Role of TiO2 coating layer on the performance of Cu2O photocathode in photoelectrochemical CO2 reduction. (9th July 2021) - Akbar, Muhammad Bilal; Gong, Yue; Wang, Yanjie; Woldu, Abebe Reda; Zhang, Xuehua; He, Tao
Abstract: TiO2 is usually employed as a protective layer for Cu2 O in photoelectrocatalytic CO2 reduction. However, the role of TiO2 layer on CO2 reduction activity and selectivity is still elusive. In this work, a systematic investigation is carried out to probe the impact of the deposition parameters of TiO2 overlayer, including the temperature and thickness, on CO2 reduction performance. Compositional and (photo-)electrochemical analysis is performed to explore the property of TiO2 overlayers. Carrier behavior, including donor density and electron energy, and stability of TiO2 are demonstrated to be influenced by atomic layer deposition conditions and thus play a role in controlling CO2 reduction reaction. Specifically, as the thickness of the TiO2 layer increases from 2 to 50 nm, the electron energy tends to be lowered accompanying the electron transfer mode from tunneling for TiO2 thin layers to type II for thick TiO2, leading to a decrease in CO2 reduction selectivity. With an increase of the TiO2 deposition temperature, the stability increases with a loss of conductivity. Cu2 O coated with 2 nm TiO2 at 150 °C is proven to be the optimized candidate in this work for photoelectrochemical reduction of CO2 to CO, HCOOH and CH3 COOH under an applied bias of −0.4 versus RHE.